2001
DOI: 10.1152/jn.2001.85.5.2088
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Plasticity at Inhibitory Synapses in Rat Striatum and Its Effects on Striatal Output

Abstract: Two forms of short-term plasticity at inhibitory synapses were investigated in adult rat striatal brain slices using intracellular recordings. Intrastriatal stimulation in the presence of the ionotropic glutamate receptor antagonists 6-cyano-7-nitroquinoxaline-2,3-dione (20 microM) and D,L-2-amino-5-phosphonovaleric acid (50 microM) produced an inhibitory postsynaptic potential (IPSP) that reversed polarity at -76 +/- 1 (SE) mV and was sensitive to bicuculline (30 microM). The IPSP rectified at hyperpolarized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 72 publications
3
19
0
1
Order By: Relevance
“…With this method, a presynaptic D 2 -mediated modulation similar to that shown on the striatopallidal pathway (Cooper and Stanford, 2001;Mengual and Pickel, 2002) or in the cholinergic or fastspiking (FS) interneurons (Pisani et al, 2000;Momiyama and Koga, 2001;Centonze et al, 2003) was shown. Similarly, a presynaptic modulation by D 1 receptor agonists as that reported in the striatonigral pathway (Floran et al, 1990(Floran et al, , 1997Cameron and Williams, 1993;Radnikow and Misgeld, 1998) was also shown, despite postsynaptic dopaminergic actions (Pacheco-Cano et al, 1996) on the subthreshold inward rectification Nisenbaum and Wilson, 1995;Mermelstein et al, 1998;Farries and Perkel, 2000) that shunts inhibitory inputs (Fitzpatrick et al, 2001).…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…With this method, a presynaptic D 2 -mediated modulation similar to that shown on the striatopallidal pathway (Cooper and Stanford, 2001;Mengual and Pickel, 2002) or in the cholinergic or fastspiking (FS) interneurons (Pisani et al, 2000;Momiyama and Koga, 2001;Centonze et al, 2003) was shown. Similarly, a presynaptic modulation by D 1 receptor agonists as that reported in the striatonigral pathway (Floran et al, 1990(Floran et al, , 1997Cameron and Williams, 1993;Radnikow and Misgeld, 1998) was also shown, despite postsynaptic dopaminergic actions (Pacheco-Cano et al, 1996) on the subthreshold inward rectification Nisenbaum and Wilson, 1995;Mermelstein et al, 1998;Farries and Perkel, 2000) that shunts inhibitory inputs (Fitzpatrick et al, 2001).…”
Section: Discussionsupporting
confidence: 52%
“…A lack of consistency in the action of dopaminergic drugs on intrastriatally evoked inhibition, as recorded in spiny cells, has been reported previously (Delgado et al, 2000;Fitzpatrick et al, 2001) and probably results from a great variety of dopaminergic actions on a diverse array of GABAergic terminals and interneurons targeting spiny cells (Lenz et al, 1994;Pisani et al, 2000;Momiyama and Koga, 2001;Bracci et al, 2002;Yasumoto et al, 2002;Centonze et al, 2003;Gao et al, 2003). When none of these actions predominate over the others in most trials, inconsistent effects should be seen.…”
Section: Ipscs From Axon Collateralsmentioning
confidence: 86%
See 2 more Smart Citations
“…Second, synaptic augmentation (30) and paired-pulse depression (29,30) have also been described for GABAergic responses to extracellular shock stimulation in striatal projection neurons. Furthermore, prolonged PSP decay at high-burst frequencies and plateau-like depolarization during such bursts are reminiscent of asynchronous GABA release that was also described in dual recordings from unidentified striatal neurons in dissociated cultures (31).…”
Section: Discussionmentioning
confidence: 99%